WOMEN’S VOICES IN MAYA ANGELOU’S SELECTED POEMS - Yulistiyanti, Yulistiyanti (Proceeding SENDI_U, 2019)
This study reveals tone of the two Maya Angelou’s poems. They are entitled Phenomenal Woman and Equality. Revealing tone needs to find out the speakers of the poems. They also convey message for the readers, so that it finds the voice of the poems. This study includes in a qualitative research that does not discuss numerical data. It describes findings of the data used. Conducting this study, the researchers did some procedures; reading the two poems as the data, identifying poems’ elements including the speaker, analyzing the tone and the message, and interpreting the data. It applies poetry theory that focuses on the intrinsic elements; tone, speaker, image, and figure of speech. From the procedures conducted, the two poems have different tone, but over all they tend to convey positive tone. Phenomenal Woman brings self-confidence tone of a woman. It has message for people, especially women, not to be embarrassed to what they have. They need care to be respected by others. Then, the second poem, Equality shows dissatisfaction and anger of a woman who experienced inequality in the society. Both poems are conveyed by women as the speakers. Keywords: poem, tone, speaker, image, Maya Angelou, Phenomenal Woman, Equality